Replacement rate and its components in Sahiwal females from birth to age at first calving - UPADHYAY, VIPIN KUMAR; MEHLA, R K; GUPTA, A K; BHAKAT, M; LATHWAL, S S; YADAV, S K (The Indian Journal of Animal Sciences, 2017)
The present study was conducted on 1,885 calving in 416 Sahiwal cows over a period of 20 years from 1994 to 2013 maintained at Livestock Research Centre, ICAR-NDRI, Karnal. The 20 years data were classified into 4 periods i.e. P1, P2, P3 and P4, each comprising of 5 years. The year of birth/calving was divided into 4 seasons, according to climatic condition of the farm as Winter, Summer, Rainy and Autumn. The parities were classified into 6 groups (first to fifth and sixth and above) and birth weight of calves was divided into 4 groups (<18, 19 to 21, 22 to 24 and >25 kg). The percentage of animals disposed off due to mortality and culling was calculated as proportion by descriptive statistics and influence of various non-genetic factors by Chi-square method using SPSS software. The overall incidence of abnormal birth in Sahiwal was 6.21% and season of birth showed significant effect on abnormal birth which was higher in autumn season (12.37%) and lower in summer season (4.28%). The overall incidence of disposal, mortality and culling was 27.35, 23.63 and 3.72% respectively, while replacement rate on female calves and total calves basis were 72.64 and 37.55% respectively. There was significant effect of period of birth and birth weight of calf on the disposal, mortality and replacement rate. The maximum mortality was observed mainly due to pneumonia and enteritis, while poor growth and debility were the principal cause of culling. It is concluded that there was significant effect of period of birth and birth weight of calves on mortality, disposal and replacement rate. Disposal rate was higher in calves born with lower birth weight; therefore, intensive feeding and healthcare management for calves born with lower birth weight will be important to minimize involuntary disposal and facilitate more number of females calves to reach to milch herd.